PENGARUH MODEL PEMBELAJARAN PEER LESSONS TERHADAP HASIL BELAJAR PPKn KELAS X IPA DI SMA NEGERI 2 PANGKALAN KURAS KABUPATEN PELALAWAN - Suryani, Erlina; Erlinda, Sri; Haryono, Haryono (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2018)
Abstract : This research is based on the low learning result of PPKn students in SMA Negeri 2 Pangkalan Kuras Kabupaten Pelalawan. The formulation of the problem in this research is: "Is there any influence of peer lessons learning model on the learning outcomes of PPKn IPA class X students in SMA Negeri 2 Pangkalan Kuras Kabupaten Pelalawan?" This research aims to know the effect of peer lessons learning model on learning outcomes of PPKn class X IPA in SMA Negeri 2 Pangkalan Kuras ". This research was conducted in SMA Negeri 2 Pangkalan Kuras in April 2018. This research is a quantitative descriptive study that became the population in this study is the students of class X IPA SMA Negeri 2 Pangkalan Kuras. Samples in this study is taken based on the technique of "Random Sampling". Where the class taken into the sample is the students of class X IPAa (experimental class) which is given the model of Peer Lessons Learning and class X IPAb (control class) are students who are given the conventional method. Then data analysis by using homogeneity test and test "t". Based on the result of research indicate that there is influence of learning result between student using Peer Lessons model and conventional method in SMA Negeri 2 Pangkalan Kuras (t = (count = 66,11)> t_ (table = 2.01)). Where there is an average increase of learning outcomes of experimental class PPKn from 66, 07 to 78.92 and the average increase in learning outcomes of control class PPKn from 58.06 to 65. Thus the hypothesis that there is influence of Peer lessons learning model on the results learning PPKn IPA class X students in SMA Negeri 2 Pangkalan Kuras, can be accepted.Keywords : Peer Lessons, Learning Outcomes.